2012
DOI: 10.1111/eva.12016
|View full text |Cite
|
Sign up to set email alerts
|

Potential for local adaptation in response to an anthropogenic agent of selection: effects of road deicing salts on amphibian embryonic survival and development

Abstract: The application of millions of tons of road deicing salts every winter in North America presents significant survival challenges to amphibians inhabiting roadside habitats. While much is known of the effects of NaCl on anuran tadpoles, less is known of effects on amphibian eggs, or any caudate life stage. In addition, little is known of the effects of MgCl2, which is now the 2nd most commonly used road deicer. Most studies have considered amphibians to be helpless victims of deicing salts, and ignore the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 51 publications
1
60
0
Order By: Relevance
“…there may be more potential for population persistence in response to 2 versus 5 ppt salinity), and it is possible that simultaneous selection from multiple stressors may impact the ability for adaptation [55]. Despite these limitations, our results, combined with those of previous studies [46,62], clearly show an intriguing pattern of strong differences in the survival of individual females' offspring in response to salinity and temperature stress, which have the potential to be important for adaptation. While responses of populations and individuals to multiple environmental stressors are clearly complex, taking into account intrapopulation variation in response to multiple, interacting stressors has the potential to provide important insights into the abilities of populations and species to persist in the future [9].…”
Section: Discussionmentioning
confidence: 81%
“…there may be more potential for population persistence in response to 2 versus 5 ppt salinity), and it is possible that simultaneous selection from multiple stressors may impact the ability for adaptation [55]. Despite these limitations, our results, combined with those of previous studies [46,62], clearly show an intriguing pattern of strong differences in the survival of individual females' offspring in response to salinity and temperature stress, which have the potential to be important for adaptation. While responses of populations and individuals to multiple environmental stressors are clearly complex, taking into account intrapopulation variation in response to multiple, interacting stressors has the potential to provide important insights into the abilities of populations and species to persist in the future [9].…”
Section: Discussionmentioning
confidence: 81%
“…This population is truly salt-naïve [44], being highly philopatric to freshwater ponds that are separated by hundreds of meters from small county roads that are not salted (Kendal Weeks, Oregon Department of Transportation Road Maintenance, personal communication; Kent Mahler, Benton County Road Maintenance, personally communication). While MgCl 2 is widely used in Oregon as its exclusive deicer, it is also not applied to the nearest stretch of highway to these ponds, located over 4 km away (Kendal Weeks, Oregon Department of Transportation Road Maintenance, personal communication).…”
Section: Methodsmentioning
confidence: 99%
“…While MgCl 2 is widely used in Oregon as its exclusive deicer, it is also not applied to the nearest stretch of highway to these ponds, located over 4 km away (Kendal Weeks, Oregon Department of Transportation Road Maintenance, personal communication). See [44] for additional details on this habitat. Eggs from wild-caught females were randomized to one of six different salt treatments, made with laboratory grade NaCl (Thermo Fisher Scientific, Fair Lawn, NJ, USA), MgCl 2 (Acros Organics, Fair Lawn, NJ, USA) and distilled water (Low NaCl, Low MgCl = 1.0 g/l Cl − ; Medium NaCl, Medium MgCl 2  = 1.5 g/l Cl − ; High NaCl, High MgCl 2  = 2.0 g/l Cl − ) and a control (20% Holtfreter's Solution = 0.7 g/l Cl − [45]).…”
Section: Methodsmentioning
confidence: 99%
“…The latter studies all demonstrated that amphibian larval survival was reduced by increases in salinity [78][79][80][81]. In fact, one study showed that for Rana temporaria, even the smallest increase in the salt concentration (500 mg/L) could cause tadpole mortality [81].…”
Section: Indirect Impacts Of Roads On Wildlifementioning
confidence: 99%